2018
DOI: 10.21834/ajqol.v3i10.104
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Degradation: Issue and awareness

Abstract: Mangroves in Malaysia reside coastlines and the largest areas of mangrove are in the Northern Sabah. They sheltered at the shores of the west coast. Over four decades, mangroves are recorded to be declining due to aquaculture practices implemented in Peninsular Malaysia. Public participation and their awareness are considered as critical components in conserving the mangrove areas. Thus, the research was conducted to discover residents' awareness towards this devastating issue. A questionnaire survey was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although persons indicated that they were aware of the issue of mangrove depletion, based on the responses to the follow-up question, it can be determined that they were not well informed on the issue. The study by Abd Rahman and Asmawi (2018), conclusively indicates that the inadequacy of awareness campaigns results in less knowledge being acquired by the locals, resulting in low involvement in mangrove management. The notable challenge in the development of local community mangrove management includes a lack of awareness of the mangroves and any issues that affect them, hence, public comprehension and awareness of mangrove ecological and economic significance are critical to maintaining sustainable management of this resource (Abd Rahman and Asmawi, 2018;Setiyaningrum, 2019).…”
Section: Awareness Of Mangrove Depletionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although persons indicated that they were aware of the issue of mangrove depletion, based on the responses to the follow-up question, it can be determined that they were not well informed on the issue. The study by Abd Rahman and Asmawi (2018), conclusively indicates that the inadequacy of awareness campaigns results in less knowledge being acquired by the locals, resulting in low involvement in mangrove management. The notable challenge in the development of local community mangrove management includes a lack of awareness of the mangroves and any issues that affect them, hence, public comprehension and awareness of mangrove ecological and economic significance are critical to maintaining sustainable management of this resource (Abd Rahman and Asmawi, 2018;Setiyaningrum, 2019).…”
Section: Awareness Of Mangrove Depletionmentioning
confidence: 95%
“…The notable piles of garbage appeared to have been transported and washed up and in from other areas. Other challenges involve rising sea levels that can overwhelm fringe mangroves, as well as global cooling and warming, that can cause range shifts as well as the loss of organisms (Abd Rahman and Asmawi, 2018;Carugati et al, 2018;Numbere, 2018).…”
Section: Seedling Datamentioning
confidence: 99%